PO.6.123 A rapid decalage of immunosuppressive therapy in a young woman with systemic lupus erythematosus. (27th September 2022) - Montozzi, G; Gamba, L; Santangeli, R; Salvucci, S; Manfredi, L; Moroncini, G
Abstract : Purpose: Autoimmune myopathies are an heterogeneous group of diseases, among which polymyositis and dermatomyositis are probably the best known. Autoimmune myositis can overlap with other autoimmune rheumatic diseases, particularly it is a rare but recognized complication of systemic lupus erythematosus (SLE). Here we report a case of SLE-related myositis, successfully treated with combined immunosuppressive therapy with rituximab and immunoglobulin infusion and then relapsed due to rapid decalage of immunosuppressive therapy with mycophenolate mofetil. Methods: A 28-year-old woman was affected from 2016 by SLE with haematological, articular and renal involvement treated with immunosuppressive therapy with good clinical response. After five years of disease remission, patient presented to the emergency department for a rapid onset of a clinical scenario with fever, alopecia, articular and muscular pain. The pharmacologic treatment was mycophenolate mofetil 500 mg/day (at this dose for about a year, after decalage by 2 gr/day), hydroxychloroquine 200 mg/day, belimumab 200 mg/week, prednisone 5 mg/day. On physical examination, she presented severe asthenia, pain on muscle palpation and loss of muscle tone with slight edema in the lower limbs. No signs of arthritis or active ulcers. Laboratory examinations revealed proteinuria > 2g/ 24h, severe increase of transaminases, phosphocreatine kinase, ANA positivity (titre1/2560) with high titres of anti-dsDNA and complementary consumption (both C3 and C4). Clinical and laboratoristic examinations raised the suspicion of SLE reactivation complicated by myositis. We performed a kidney biopsy with histological examimation suggestive for class IV lupus nephritis and an electromyography with a pattern of myositis. So we decided, according to disease involvement, to begin treatment with Rituximab (four administrations, 375 mg/m2) and gradual reintroduction of full-dose mycophenolate mofetil therapy (2 g/day). Results: Disease activity was high so immunosuppressive therapy with high-dose corticosteroids, Rituximab and mycophenolate mofetil was started with subsequent good clinical response. One month after the infusion of Rituximab, muscle enzymes were yet elevated thus we added therapy with endovenous immunoglobulin with discrete clinical and laboratory improvement. Conclusions: Pharmacological treatment with rituximab and endovenous immunoglobulin can be considered as a good and safe therapeutic option for clinical management of SLE-related myositis. This clinical case underlines the importance of maintaining immunosuppressive treatment for a long period, and to decrease dose very slightly, when disease is in long remission.